2019
DOI: 10.1021/acs.cgd.9b00846
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of a New Facile Ligand in a Dual Role: Mechanically Elastic Crystal and Selective Mitochondria Target

Abstract: Herein we report the unique properties of a new Schiff base ligand (H 2 L), synthesized and characterized by Fourier transform infrared spectroscopy, 1H and 13C NMR, and liquid chromatography-mass spectrometry. Further, it has been authenticated by a single-crystal X-ray diffraction (XRD) study. In a solid state, H 2 L can bend upon an externally applied stress and rapidly reverts to its original shape upon relaxation, revealing highly flexible and elastic bending properties. Powder XRD and Raman studies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 69 publications
0
15
0
Order By: Relevance
“…Recently, the investigation of flexible luminescent materials (FLCs) burgeons the cutting-edge fields of smart materials. However, such prosperity certainly took a long time. Ghosh and Reddy were pioneers in the research of flexible crystals, since they reported the needle cocrystals which were formed from caffeine, 4-chloro-3-nitrobenzoic acid, and methanol, displaying elastic bending capacity upon applied stress .…”
mentioning
confidence: 99%
“…Recently, the investigation of flexible luminescent materials (FLCs) burgeons the cutting-edge fields of smart materials. However, such prosperity certainly took a long time. Ghosh and Reddy were pioneers in the research of flexible crystals, since they reported the needle cocrystals which were formed from caffeine, 4-chloro-3-nitrobenzoic acid, and methanol, displaying elastic bending capacity upon applied stress .…”
mentioning
confidence: 99%
“…[9] Up to now, based on the above theoretical basis, a series of elastic crystals had been designed and reported by researcher. [10][11][12][13][14][15][16][17][18] Recently, MuMurtrie's group had reported an elastic crystal based on metal-organic complex copper (II) acetylacetonate, which revealed the elasticity of the crystal originating from the molecule rotation under applied stress.This work provided a new idea for the design of elastic crystals. [19] However, the above-mentioned bending was only limited to single-faced bending, and there were very few reports of multifaceted bending.…”
Section: Introductionmentioning
confidence: 99%
“…prepared and analyzed many N‐Benzylideneanilines crystals, and found that the elastic crystals had the following characteristics: 1) interlocking molecular packing patterns, 2) weak and dispersive interactions [9] . Up to now, based on the above theoretical basis, a series of elastic crystals had been designed and reported by researcher [10–18] . Recently, MuMurtrie's group had reported an elastic crystal based on metal–organic complex copper (II) acetylacetonate, which revealed the elasticity of the crystal originating from the molecule rotation under applied stress.This work provided a new idea for the design of elastic crystals [19] .…”
Section: Introductionmentioning
confidence: 99%
“…As a family of functional materials, organic crystals with long-range molecular packing structures as well as anisotropic properties have drawn increasing attention in the past two decades because of their wide applications in organic light-emitting diodes, detectors, optical waveguide, organic solid-state lasers, etc. However, organic crystals are generally brittle and thus it is quite difficult to process them, which limits their applications to a great extent. , Therefore, mechanically deformed organic crystals have recently become a cutting-edge research field. Technically, the flexibility of organic crystals can be categorized into two types, reversible elastic deformation and irreversible plastic deformation. Desiraju first observed plastic deformation in the bulk organic crystals 2-(methylthio)­nicotinic acid featured an anisotropic molecular arrangement in 2006 .…”
mentioning
confidence: 99%